Adverse Interaction between Capecitabine and Warfarin Resulting in Altered Coagulation Parameters: A Review of the Literature Starting from a Case Report - Giovanni Giunta (Case Reports in Medicine)
Capecitabine is an orally active prodrug of fluorouracil and is extensively used as an antineoplastic agent. It is converted to 5-Fluorouracil in the liver and tumor tissues. Warfarin is an anticoagulant agent for preventing and treating venous and arterial thrombosis and embolism and is metabolized by cytochrome P450 isoenzymes in the liver. Preclinical in vitro studies using human liver microsomes report no inhibitory effects between capecitabine and substrates of cytochrome P. However, the concomitant administration of capecitabine and warfarin resulted in INR elevation in the cases previously reported in the literature. The exact mechanism of this interaction is unknown but may be related to downregulation of cytochrome P450 2C9 by capecitabine or its metabolites. We report on the possible adverse interaction between capecitabine and warfarin in a patient with metastatic breast cancer and critically review the existing literature on this topic. Physicians should be aware of adverse reactions arising from the combined use of capecitabine and warfarin. In the light of the current data, INR levels should be closely monitored in patients using these drugs together.